ОНКОЛОГИК БЕМОРЛАРДА КАСАЛЛИКНИНГ ИЧКИ МАНЗАРАСИ - Уразбаева, Д.А. (SCIENCE and SOCIETY, 2020)
The article deals with the issues of hecessity of studying the inside picture of the disease of cancer patients. One of the basic psychological problems in oncological hospitals is the relation and reaction of aperson to the disease.